Talent Management and Development in the United Arab Emirates. Issue 4 (November 2018) - Dirani, Khalil; Bowman, Eric; Guyer, Thomas; Kasper, Richard; Makarem, Yasmeen; Ray, Sarah; Wang, Chih-Wei; Xie, Lei
The Problem: Although there is a surge in research on Talent management and talent development (hence forward TMD) practices across different regions, most of what we know about these topics in the United Arab Emirates (UAE) is based on government and practitioners' reports. Nowadays, UAE is going through unprecedented times of growth. Organizations are operating in a diverse environment created by a smart government vision and practical policies that allowed the UAE to be labeled as a talent magnet destination. Still, TMD activities seem to be influenced by a two-tier system, one for Emirati nationals and another for expatriates. The question is whether the UAE is able to continue its growth through current TMD practices or whether a more strategic approach is needed to address the current TMD challenges and to meet the needs of individuals and of organizations. The Solution: The purpose of this article is to provide an overview of professionals' perspectives in different sectors about (a) the government policies, (b) current activities, and (c) challenges and contextual factors that affect the current state of TMD in the country. Once we understand the different policies, activities, and challenges, practitioners and leaders can use TMD as a source of power, or a strategy, that can lead people and organizations into success. The Stakeholders: Human resources and organization development experts working in international contexts, administrators in academic institutions, and leaders in government organizations interested in HRD in the context of the UAE, will find the information presented in this study useful.